2015
DOI: 10.1177/2040622315569501
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle measures in the management of gastro-oesophageal reflux disease: clinical and pathophysiological considerations

Abstract: Several lifestyle and dietary factors are commonly cited as risk factors for gastrooesophageal reflux disease (GORD) and modification of these factors has been advocated as first-line measures for the management of GORD. We performed a systematic review of the literature from 2005 to the present relating to the effect of these factors and their modification on GORD symptoms, physiological parameters of reflux as well as endoscopic appearances. Conflicting results existed for the association between smoking, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 128 publications
(148 reference statements)
1
34
0
Order By: Relevance
“…48 The systematic review conducted by Kang et al suggests that studies on acid and spicy foods are not as many as studies on fatty foods and the results varry. 42 Some studies supported the abovementioned statement; while others suggest that there is no correlation between GERD complaints and the consumption of acid or spicy foods. 6,9,46,[48][49][50][51] Coffee Similar to studies on alcohol, varied results have also been found in studies which evaluate the correlation between coffee consumption and GERD complaints.…”
Section: Acid and Spicy Foodsmentioning
confidence: 95%
See 4 more Smart Citations
“…48 The systematic review conducted by Kang et al suggests that studies on acid and spicy foods are not as many as studies on fatty foods and the results varry. 42 Some studies supported the abovementioned statement; while others suggest that there is no correlation between GERD complaints and the consumption of acid or spicy foods. 6,9,46,[48][49][50][51] Coffee Similar to studies on alcohol, varied results have also been found in studies which evaluate the correlation between coffee consumption and GERD complaints.…”
Section: Acid and Spicy Foodsmentioning
confidence: 95%
“…The mechanism of smoking which leads to the development of re u symptom is correlated to reduced pressure of lower esophageal sphincter during smoking, reduced bicarbonate from the saliva and increased intra-abdominal pressure when coughing or having deep inspiration. 6,42 Studies conducted by Diaz-Rubio et al and Bhatia et al have reported that there is no signi cant correlation between smoking habit and GERD complaints. 7,9 Meanwhile, a study conducted by Sharma et al has found that GERD complaints are more frequently found in active smokers.…”
Section: Correlation Between Smoking and Gerdmentioning
confidence: 99%
See 3 more Smart Citations